Phenolic quality in grape cultivars submitted to green pruning and hormonal regulator (Research, Society and Development, 2021)
The color and stability of anthocyanins in fruits are largely influenced by temperature, light and pH. In this sense, the present work aimed to evaluate the management of defoliation and the application of abscisic acid (S-ABA) in the phenolic quality of the cultivars Primitivo and Malbec (Vitis vinifera L.). The experiment was conducted in a commercial vineyard in Santa Catarina, Brazil, with two cultivars of vine Primitivo and Malbec (V. vinífera L.), respectively, for two consecutive cycles: 2015/2016 and 2016/2017. The experimental design was in randomized blocks, consisting of six treatments: 1) control (without treatment); 2) manual defoliation at the beginning of maturation (DIM); 3) manual defoliation fifteen days after the first defoliation (D15); 4) S-ABA 200 mg L-1 (ABA200); 5) S-ABA 400 mg L-1 (ABA400); 6) S-ABA 600 mg L-1 (ABA600), four replicates and three plants per plot. With the data obtained, the Kolmogorov-Smirnov normality test was performed at the 5% level of significance, using analysis of variance (ANOVA) and, subsequently, Principal Component Analysis (ACP) in order to analyze the relation between the analyzed parameters, using the software R. After the discussion of the results, it is concluded that the exogenous application of S-ABA provides higher levels of total flavonoids, luminosity and chromaticity in cvs grapevines. Malbec and Primitivo and that the application of S-ABA promoted defoliation with 600 mg L-1, which can be an alternative to reduce production costs. Defoliation provided an increase in color intensity and Hue angle in cv. Malbec and Primitivo, in which this factor may be related to the higher incidence of radiation in the bunches, caused by the removal of the leaves.